State of histostructure of liver and of exocrine pancreas tissues in experimental diabetes caused by diabetogenic metabolites of tryptophan - Meyramov, G.G.; Kohnert, K.-D.; Kikimbaeva, A.A.; Meyramova, A.G. (Изд-во КарГУ, 2013)
Authors showed new experimental data on the state of histostructure of Liver and Exocrine Pancreas tissue in experimental diabetes approached on conditions of development to human 2 type diabetes caused by 4,8-dihydroxyquinolin-2-carboxylic acid — the substance actively synthesized in elderly human, unlike all known today more than 30 diabetogenic substances. It is established that, at the same time with destruction of pancreatic B-cells that is a direct cause of diabetes, a multiple destructive changes are developed in a Liver and in Exocrine tissue of Pancreas. Authors suppose these changes which are not belong to direct causes of developed diabetes, but can aggravate diabetes considerably.
Keywords: pancreatic islets; B-cells; liver; experimental diabetes; distrophya; necrosis; destruction of cells; diabetogenic chemicals; diabetogenic metabolites of tryptophan; hydropic degeneration